Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-3 Multipying Powers with the Same Base - Practice and Problem-Solving Exercises: 59

Answer

$\dfrac{1}{a}$

Work Step by Step

(i) $a^m \cdot a^n = a^{m+n}$ (ii) $a^{-m} = \dfrac{1}{a^m}, a \ne 0$ Use the rules above to obtain: $=\dfrac{1}{a^{4+(-3)}} \\=\dfrac{1}{a^{1}} \\=\dfrac{1}{a}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.